2015
DOI: 10.5194/tc-9-479-2015
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Organic carbon pools in permafrost regions on the Qinghai–Xizang (Tibetan) Plateau

Abstract: Abstract. The current Northern Circumpolar Soil Carbon Database did not include organic carbon storage in permafrost regions on the Qinghai–Xizang (Tibetan) Plateau (QXP). In this study, we reported a new estimation of soil organic carbon (SOC) pools in the permafrost regions on the QXP up to 25 m depth using a total of 190 soil profiles. The SOC pools were estimated to be 17.3 ± 5.3 Pg for the 0–1 m depth, 10.6 ± 2.7 Pg for the 1–2 m depth, 5.1 ± 1.4 Pg for the 2–3 m depth and 127.2 ± 37.3 Pg for the layer of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 50 publications
7
106
1
1
Order By: Relevance
“…We found significant positive correlations between BPC with SOC at depths of 0–50 cm, which indicates that BPC was likely the main source and dominant influence of SOC density in the upper reaches of the Shule River Basin. This is consistent with the results of other studies that identify plant roots as a major source of SOC 38,4244 . In addition, the stepwise linear regression analysis results show that SM accounts for the greatest amount of spatial variation in BPC (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…We found significant positive correlations between BPC with SOC at depths of 0–50 cm, which indicates that BPC was likely the main source and dominant influence of SOC density in the upper reaches of the Shule River Basin. This is consistent with the results of other studies that identify plant roots as a major source of SOC 38,4244 . In addition, the stepwise linear regression analysis results show that SM accounts for the greatest amount of spatial variation in BPC (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Their results showed that the storage of soil organic carbon, total nitrogen, and soil inorganic carbon is higher in permafrost than in the overlying active layer. Combined with results from previous studies, Mu et al (2015b) recently found that the average soil organic content in permafrost regions over the Qinghai-Tibetan Plateau is higher than that in the Arctic and subarctic. Their results show that the total carbon storage in permafrost regions of the northern hemisphere is about 1832 Pg, approximately 2.5 times greater than the current atmospheric carbon content.…”
supporting
confidence: 66%
“…The amount of organic carbon in the Tibetan and North China region is currently estimated at 35.7 Pg (Luo et al 2000;Mu et al 2015;Ding et al 2016). Simple calculations based on extremely limited data suggest that another ~350-465 Pg C can be found in additional deep terrestrial deposits, although more sampling and data synthesis need to be done to verify or revise these potential deep permafrost carbon deposits (Schuur et al 2015).…”
Section: Sidebar 53: Permafrost Soil Carbon Pool: Quantifying a Potementioning
confidence: 99%